Shakespeare Against Authoritarianism and Totalitarianism in the World of Globalisation - Dumitrašković Tatjana (Romanian Journal of English Studies, 2020)
Critics belonging to cultural materialism consider that Shakespeare’s work has its own political dimension by demystifying specific forms of power. The paper deals with the way Shakespeare’s three great tragedies reveal how the authoritarian power could function through terror based on violence and dictatorship, and the abuse of that power in the world of globalisation.